Membangun Keterampilan Kepemimpinan Mahasiswa dengan Mengajarkan Teknik Hidroponik kepada Siswa SD - Zahara, Laxmi; Zul Hidayatullah; Nunung Ariandhani (Jurnal Teknologi Informasi untuk Masyarakat, 2024)
This community service program aims to develop leadership skills among university students through practical learning by teaching hydroponic techniques to elementary school (SD) students. Hydroponics was chosen as it is effective for maximizing the use of limited space and supports environmental management through the use of plastic waste as planting media. This three-month program was conducted at SDN 3 Sekarteja, involving 5th and 6th-grade students in hands-on activities of growing vegetables without soil. The program results showed an increase in students' understanding of hydroponic techniques from 40% to 85%, as well as high enthusiasm and active participation throughout the activities. Besides introducing modern agriculture to elementary students, the program successfully honed the leadership skills of university students in a real-world context. By involving various stakeholders, including teachers and parents, this initiative is expected to have a long-term impact on sustainable agriculture education and food independence among the younger generation.